Evaluation and Microsimulation of Road Segment Performance in Densely Populated Areas Using PTV Vissim ( Case Study: P Suryanata Street, Samarinda) - Pitoyo, Pitoyo; Badiuzaman, Achmad (LPPI Universitas Muhammadiyah Kalimantan Timur (UMKT), 2024)
Prince Suryanata Street is a connecting road between the North Samarinda District of Samarinda City and the Tenggarong District of Kutai Kartanegara Regency. Frequent congestion of all types of vehicles, both entering and exiting the center of Samarinda City, causes traffic jams on this road segment. Additionally, the high population density in the area around Prince Suryanata Street also contributes to the heavy traffic. The traffic problems on Prince Suryanata Street in Samarinda City are now being felt by road users. One issue that further worsens the traffic conditions is the poor performance of the road segments. Therefore, an evaluation of the road is necessary. The traffic flow volumes are as follows: Monday, 9834.75 pcu/hour; Friday, 5911.95 pcu/hour; and Saturday, 5690.8 pcu/hour. The highest traffic volume occurs on Monday due to various school activities and community activities around the observation location. The analysis results show that Prince Suryanata Street experiences high traffic density, especially during peak hours, leading to a decline in road service quality. The current capacity (C) is 244.76 pcu/hour, the degree of saturation (ds) is 1.68, and the Level of Service (LoS) is rated at class F. For the 10-year forecasting, the projected capacity (C) is 6397.44 pcu/hour, the degree of saturation (ds) is 0.95, and the Level of Service (LoS) is anticipated to be in class D.